Predicting symptom clusters of posttraumatic stress disorder (PTSD) in Croatian war veterans: the role of socio-demographics, war experiences and subjective quality of life - Lončar Mladen (Array, 2014)
Background: Previous research has documented multiple chains of risk in the development of PTSD among war veterans. However, existing studies were mostly carried out in the West, while they also did not analyze specific symptom clusters of PTSD. The aim of this study was to examine the role of socio-demographic characteristics, war experiences and subjective quality of life in the prediction of three clusters of PTSD symptoms (i.e., avoidance, intrusion, hyperarousal). Subjects and methods: This study comprised 184 male participants who have survived war imprisonment during the Croatian Homeland War in the period from 1991 to 1995. The data was collected through several self-report measuring instruments: questionnaire on socio-demographic data, war experiences (Questionnaire on Traumatic Combat and War Experiences), subjective quality of life (WHO-Five Well-being Index), and PTSD symptoms (Impact of Events Scale - Revised). Results: The level of three symptom clusters of PTSD was found to be moderate to high, as indicated by the scores on the IES-R. Results of the three hierarchical regression analyses showed the following: traumatic war experiences were significant predictors of avoidance symptoms ; traumatic war experiences and subjective quality of life were significant predictors of hyperarousal symptoms ; and traumatic war experiences, material status and subjective quality of life were significant predictors of intrusion symptoms. Conclusions: These findings support the widespread belief that the development of war-related PTSD is accounted for by multiple chains of risk, while traumatic war experiences seem to be the only predictor of all three symptom clusters. Future research should put more emphasis on specific PTSD symptom clusters when investigating the etiopathogenesis of this disorder among waraffected populations.